Trilingualism in Hong Kong: A World Englishes Framework for EMI English Teachers in University - Chan, Ka Long Roy (LEARN Journal: Language Education and Acquisition Research Network, 2023)
With the rise of multilingualism and the use of a local variety of English in Hong Kong, the current article proposes a framework for EMI teacher training for university teachers (WEMTT-Framework) to expose them not only to a theory of World Englishes but also a practicum of teaching in multilingual settings. Even though Hong Kong has been regarded as a trilingual (Cantonese-English-Mandarin) city where English is taught as a second language, the EMI teaching in Hong Kong is still highly exonormative-oriented. With an increasing number of studies revealing the possibility of EMI teaching with the help of multilingual and World Englishes elements, the current paper also explores how World Englishes and multilingualism help in the present EMI teaching environment. The framework and the discussion are not only applicable to Hong Kong but also places with similar multilingual settings, thus expanding to many Asian cities with colonial backgrounds. The paper ends with a call for action from educators and researchers to work on the implementation of teacher training and carry out further studies in different settings.